Crustal structure beneath Namche Barwa, eastern Himalayan syntaxis: New insights from three‐dimensional magnetotelluric imaging. Issue 7 (26th July 2017) - Lin, Changhong; Peng, Miao; Tan, Handong; Xu, Zhiqin; Li, Zhong‐Hai; Kong, Wenxin; Tong, Tuo; Wang, Mao; Zeng, Weihua
Abstract: The eastern terminations of the Himalayan orogeny, named Namche Barwa, are considered a vital natural laboratory in the Tibetan plateau for geodynamics due to its distinctive geological and geomorphological characteristics. Magnetotelluric (MT) data measured at 83 sites around the Namche Barwa are imaged by three‐dimensional (3‐D) inversion to better reveal the crustal structure of the eastern Himalaya. The results show a complex and heterogeneous electrical structure beneath the Namche Barwa. The electrical conductors distributed in the middle and lower crust around the Namche Barwa provide additional evidence for the "crustal flow" model if they are considered as some parts of the flow in a relatively large‐scale region. The near‐surface resistivity model beneath the inner part of Namche Barwa conforms with the locations of hot spring and fluid inclusions, the brittle‐ductile transition, and the 300°C–400°C isotherm from previous hydrothermal studies. Relatively resistive upper crust (>800 Ωm) is underlain by a more conductive middle to lower crust (<80 Ωm). The electrical characteristics of the thermal structure at shallow depth indicate an accumulation of hydrous melting, a localized conductive steep dipping zone for decompression melting consistent with the "tectonic aneurysm" model for explaining the exhumation mechanism of metamorphic rocks at Namche Barwa. The results also imply that both surface processes and local tectonic responses play a vital role in the evolution of Namche Barwa. An alternative hypothesis that the primary sustained heat source accounts for the local thermal‐rheological structure beneath Namche Barwa is also discussed. Key Points: We present new reticular MT data and 3‐D inversion results of Namche Barwa Our results at Namche Barwa provide additional evidence to the crustal flow model Our results on the inner part of the Namche Barwa support the "tectonic aneurysm" model